1960
DOI: 10.1104/pp.35.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution, and Destruction of Indoleacetic Acid in Plum Stem Cuttings

Abstract: Rooting of greenwood cuttings of Marianna 2624plum (Priunus cerasifera Ehrh. X P. munsoniana Wight & Hedr.) taken in spring or summer is dependent on the presence of a certain minimum leaf area.Treatment of the basal portion of the cuttings with indoleacetic (IAA) or indolebutyric acid (IBA) sub-stantially increases the number of roots per cutting (20). The site of the auxin action is not known. Perhaps there is a direct effect at the site of application wlhere roots appear. Another possibility is that auxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

1961
1961
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
(15 reference statements)
1
10
0
1
Order By: Relevance
“…According to Hartmann et al [2], one of the best rooting promoters is the IBA due to its fast auxin activity and an enzymatic system of fairly slow destruction. Strydum and Hartman [11] compared respiration level of treated cuttings with exogenous auxin and control plants; he found that positive effect of auxin is related to increase of level of respiration, high level of amino acid storage at the base of cuttings 24 hours after treatment with auxin. These processes occur simultaneously with increased nitrogen material content at the base of cuttings that move toward upper part of cutting as asparagine does.…”
Section: Healing Percentage and Root Indicesmentioning
confidence: 99%
“…According to Hartmann et al [2], one of the best rooting promoters is the IBA due to its fast auxin activity and an enzymatic system of fairly slow destruction. Strydum and Hartman [11] compared respiration level of treated cuttings with exogenous auxin and control plants; he found that positive effect of auxin is related to increase of level of respiration, high level of amino acid storage at the base of cuttings 24 hours after treatment with auxin. These processes occur simultaneously with increased nitrogen material content at the base of cuttings that move toward upper part of cutting as asparagine does.…”
Section: Healing Percentage and Root Indicesmentioning
confidence: 99%
“…These conjugates have been observed to form only in intact tissues, while in homogenized tissue extracts the IAA molecule is degraded by oxidative decarboxylation, ring opening, or both (8). In previous studies by others on IAA metabolism of intact tissues using radioactive IAA labeled in the side-chain (5,11) it was found that the carboxyl group (-1-C14) and, after a lag period, the methylene group (-2-C'4) yielded respiratory C'140,; the chemical nature of the dlecarboxylated metabolites remained unknown.…”
mentioning
confidence: 99%
“…One such example is the dependency of rooting of some cuttings on a certain minimum leaf area (e.g. Strydom & Hartmann, 1960). The general observation that the presence of leaves markedly enhances the response of cuttings to supplied auxin has been widely accepted as evidence for the existence of other specific ' leaf factors' essential for root formation (e.g.…”
Section: Resultsmentioning
confidence: 99%